Employee work stress based on gender differences during the COVID-19 Pandemic - Syafrizaldi Syafrizaldi (Institut Agama Islam Negeri Langsa, 2020)
This study aims to see employee work stress reviewed from gender differences during the Covid-19 Pandemic. This research involved employees at PT. Saka Mitra Sejati Medan. The results showed that there was a difference in work stress between male and female employees. The statistical calculations of empirical mean scores showed that subjects of the male gender had a lower average empirical mean score of 29.67, while the average empirical mean value of female subjects was 30.47. Thus, during the Pandemic, female employees had higher levels of work stress compared to male employees.